Welcome to our place! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
'Spore: Karibu kwetu!', writes Ghislain Somba Byombo, from the Democratic Republic of Congo. Working for the Gilman International Conservation NGO, he makes out a case for the conservation of national parks. 'Believe us, Spore teaches and enlightens...